Attenuation in Comments on Digital News in Spanish and Chilean Newspapers [la Atenuación en Los Comentarios Sobre Las Noticias Digitales en Periódicos de España y Chile] - Moya-Munoz, P (Pontificia Universidad Catolica de Chile, 2018)
The objective of this research is to identify the variation in the use of attenuation strategies used by digital newspaper commentators of El País (Spain) and Emol (Chile) in two contexts, politics and sports. In this analysis we consider attenuation as part of interactional metadiscourse analysis, that is, those elements that indicate the decision of writers to recognize different points of views to not compromise themselves with a proposition (Hyland, 2005). In this study, we compiled a corpus of 2,400 comments; then it was analyzed with the tool UAM Corpus Tool to detect the discourse markers used to attenuate the digital comments to digital news. The results indicated that, on the one hand, the comments from El País included more attenuators than the comments included in Emol. On the other hand, it was observed that there was no difference in the use of attenuators if we consider the two specific contexts analysed, i.e. politics and sports. © 2018 Pontificia Universidad Catolica de Chile. All rights reserved.